Morpho-agronomic assessment of introductions of butternut squash (Cucurbita moschata Duch.) from Central America (2017)
A Central American collection of butternut squash (Cucurbita moschata Duch.) was characterized based on a series of morpho-agronomic descriptors and its variability assessed. Floral asynchrony ranging from 10 to 15 days was observed between staminate and pistillate flowers. Differences were also observed among introductions for all quantitative characteristics evaluated (P0.01). An interaction between introduction and planting cycle (P0.05) was observed for 50% of the evaluated variables: fruit weight, polar diameter of fruit, wall thickness of fruit, fruit color, days to harvest, and total fruit seed weight. Cluster analysis revealed that groups 3 and 5 gathered introductions presenting high yields and larger, heavier fruits. Group 4 gathered introductions with intermediate yields, high seed production, and thick fruit walls. In all cases, genetic improvement aiming to increase the production of fruit for fresh consumption or agro-industrial purposes as well as the production of oilseed should use introductions from groups 3 and 5 in well-planned crossings with introductions from group 4.